The Implementation of Legal Protection for Minor Victims of Sexual Violence: An Empirical Study in Kronjo District, Tangerang Regency, Banten Province - Apriyanti, Astri; Habeahan, Rasman; Nasir, Muh (UIN Jakarta, 2026)
The implementation of legal protection for child victims of sexual violence in the studied area has been carried out; however, it has not yet reached optimal effectiveness. Strengthening inter-agency coordination, enhancing the capacity of law enforcement officials, and increasing public awareness are necessary to establish a more comprehensive and equitable child protection system. This study addresses the following research questions: (1) How is the current implementation of legal protection for minor victims of sexual violence in Kronjo District, Tangerang Regency? and (2) What factors hinder the effective implementation of such legal protection? Accordingly, this research aims to analyze both the implementation and the challenges faced in protecting minor victims of sexual violence in the region. The research employs an empirical juridical method with a qualitative approach. Data were collected through literature review and field research, including interviews with law enforcement officers, victim advocates, and other relevant stakeholders. Data analysis was conducted descriptively and analytically, with reference to applicable laws and regulations, particularly those concerning child protection. The findings indicate that the implementation of legal protection for child victims of sexual violence in Kronjo District remains suboptimal. This is reflected in several obstacles, including procedural challenges in case handling, limited inter-agency coordination, insufficient human resources, and low public awareness regarding child protection. Nevertheless, protective measures are still carried out through legal processes, psychological assistance, and social rehabilitation for victims. Keywords: legal protection, minors, sexual violence, implementation, victims